RELATIONSHIPS BETWEEN PHYSIOLOGY, GROWTH, AND YIELD OF CEREAL CROPS UNDER WATERLOGGING STRESS - Erlinda Diantini; Hidya Nurlita; Aep Wawan Irwan; Fiky Yulianto Wicaksono (Gunung Djati Conference Series, 2026)
Global food security is increasingly threatened by abiotic stresses, particularly waterlogging, which poses significant challenges to cereal crop production. Waterlogging is one of the primary abiotic stresses that significantly influence the interrelationships among plant physiology, growth, and yield. This review aims to examine the relationships among these three aspects in cereal crops, with an emphasis on the response mechanisms to waterlogging stress. Findings from the reviewed literature indicate that waterlogged conditions induce hypoxia in the root zone, leading to reduced photosynthetic rates, impaired nutrient uptake, and increased production of reactive oxygen species (ROS), which trigger cellular damage. These effects result in reduced plant growth and yield. Nevertheless, plants exhibit various adaptive mechanisms, such as aerenchyma formation, adventitious root development, and proline accumulation, which enhance tolerance to stress. Variations in tolerance levels among cereal species also influence the extent of yield reduction. Overall, improving plant tolerance to waterlogging stress requires an integrated approach through physiological understanding, genetic improvement, and the application of appropriate agronomic management.